ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN SITUS BERITA SUARAMERDEKA.COM DENGAN SIKAP TERHADAP PENGGUNAAN SEBAGAI VARIABEL INTERVENING - Widyananda, Muthia Hanum; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2018)
A site's traffic is one of the most important performance indicators in a company that provides digital content or a website. This research aims to analyze the influence of perceived ease of use and perceived usefulness towards intention to use news sites Suaramerdeka.com through attitude towards use as the intervening variable. The sampling method used on this research is non-probability samplig with purposive sampling technique. Samples were collected from 100 respondents on Semarang who use the internet and knows information about Suaramerdeka.com. Analysis method used here is multiple regression analysis wich includes validity test, reliability test, classic assumption test, multiple linier regression test, t-test, f-test, determination test and sobel test. The result showed that perceived ease of use and perceived usefulness has positive and significant influence on attitude towards use. While attitude towards use as the intervening variable has positive and significant influence on intention to use